Forest carbon stocks increase with higher dominance of ectomycorrhizal trees in high latitude forests - Guoyong Yan; Chunnan Fan; Junqiang Zheng; Guancheng Liu; Jinghua Yu; Zhongling Guo; Wei Cao; Lihua Wang; Wenjie Wang; Qingfan Meng; Junhui Zhang; Yan Li; et al. (Nature Communications, 2024)
Abstract Understanding the mechanisms controlling forest carbon accumulation is crucial for predicting and mitigating future climate change. Yet, it remains unclear whether the dominance of ectomycorrhizal (EcM) trees influences the carbon accumulation of entire forests. In this study, we analyzed forest inventory data from over 4000 forest plots across Northeast China. We find that EcM tree dominance consistently exerts a positive effect on tree, soil, and forest carbon stocks. Moreover, we observe that these positive effects are more pronounced during unfavorable climate conditions, at lower tree species richness, and during early successional stages. This underscores the potential of increasing the dominance of native EcM tree species not only to enhance carbon stocks but also to bolster resilience against climate change in high-latitude forests. Here we show that forest managers can make informed decisions to optimize carbon accumulation by considering various factors such as mycorrhizal types, climate, successional stages, and species richness.